Estudio y diseño del sistema de agua potable, alcantarillado sanitario y alcantarillado pluvial para la ciudadela El Pescador, parroquia Unión Lojana, cantón Huaquillas, provincia de El Oro. - Gadvay Requelme, Lisseth Priscila (2015)
The designs proposed in the case of Potable Water System corresponds to a Branched or open network connected to a pipe 90 mm ​​PVC which is supplied the vital liquid by the new drinking water plant of Arenillas , for sanitary sewer it corresponds to a conventional type of level 3, which works to gravity, connected to a pit major overhaul that evacuates sewage to New Oxidation ponds city of Huaquillas , the storm sewer is a system of conventional type level 3 and desfoga rains to Estero El Robalo waters.